2017
DOI: 10.1007/s00394-017-1468-1
|View full text |Cite
|
Sign up to set email alerts
|

High protein intake along with paternal part-time employment is associated with higher body fat mass among girls from South China

Abstract: Our data indicate that school-aged girls, but not boys, living in South China with higher dietary protein intake might have higher body fat mass, which could be modified by paternal occupation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As a modifiable factor, dietary intake has played an important role in the development of childhood overweight/obesity. In the CAC study, girls, but not boys, with higher dietary protein intake may have higher body fat mass, which, further modified by paternal occupation, was observed only in girls with parttime working fathers (28). Also, children with healthy dietary patterns (i.e., beans, potatoes, whole grains, dairy) were at lower risk for overweight/obesity (OR = 0.59, 95% CI [0.39, 0.90]) (30).…”
Section: Obesitymentioning
confidence: 74%
See 1 more Smart Citation
“…As a modifiable factor, dietary intake has played an important role in the development of childhood overweight/obesity. In the CAC study, girls, but not boys, with higher dietary protein intake may have higher body fat mass, which, further modified by paternal occupation, was observed only in girls with parttime working fathers (28). Also, children with healthy dietary patterns (i.e., beans, potatoes, whole grains, dairy) were at lower risk for overweight/obesity (OR = 0.59, 95% CI [0.39, 0.90]) (30).…”
Section: Obesitymentioning
confidence: 74%
“…Obesity and protein intake Girls, but not boys, with higher dietary protein intake might have higher body fat mass (28).…”
Section: Obesitymentioning
confidence: 99%
“…Similarly, several studies reported positive associations between dietary intake of protein as percentage of total energy and adiposity indices, while those studies only presented results with or without adjustment of total energy intake [6][7][8][9][10]21]. So far as we know, there is no clear picture to what degree this positive association could be attributable to the energy contribution of protein intake.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, approximately one-fourth of the world diabetes patients live in China [20], and over 60% of those with diabetes were unware of their diagnosis, with no clear treatment of glycaemic control. The evidence was quite limited for the associations between macronutrient intake and adiposity or glycaemic control across the country, given a handful of regional studies [15,[21][22][23]. Therefore, the present study was aimed to evaluate the cross-sectional association of macronutrient intake, with an emphasize on protein, with adiposity and glycaemic control indices, among a nation-wide sample in China.…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of SCCNG study participants started in March 2013 in Sichuan Province, Guizhou Province and Chongqing Municipality, which are located in Southwest China. Details on the subject selection procedure and the study protocol have been described elsewhere [ 34 ]. In brief, for the yearly recruitment from 2013 onwards eligible participants were children aged 6–8 years in 23 selected primary schools who are cooperative and voluntary at the time of recruitment.…”
Section: Methodsmentioning
confidence: 99%